Different Cellular Response of Human Mesothelial Cell MeT-5A to Short-Term and Long-Term Multiwalled Carbon Nanotubes Exposure. (8th August 2017) - Ju, Li; Wu, Wei; Yu, Min; Lou, Jianlin; Wu, Hao; Yin, Xianhong; Jia, Zhenyu; Xiao, Yun; Zhu, Lijin; Yang, Jun
Abstract : Despite being a commercially important product, multiwalled carbon nanotubes (MWCNTs) continue to raise concerns over human health due to their structural similarity to asbestos. Indeed, exposure to MWCNT has been shown to induce lung cancer and even mesothelioma, but contradictory results also exist. To clarify the potentially carcinogenic effects of rigid and rod-like MWCNT and to elucidate the underlying mechanisms, the effects of MWCNT on human mesothelial cell MeT-5A were examined throughout 3 months of continuous exposure, including cytotoxicity, genotoxicity, and cell motility. It was found that MWCNT did not affect MeT-5A cell proliferation at 10  μ g/cm 2 within 72 h treatment, but under the same condition, MWCNT induced genotoxicity and perturbed cell motility. In addition, MeT-5A cells demonstrated different cellular responses to MWCNT after short-term and long-term exposure. Taken together, our results indicated a possible carcinogenic potential for MWCNT after long-term treatment, in which Annexin family proteins might be involved.